Evaluation of the possible association of PDCD-1 and LAG3 gene polymorphisms with hepatocellular carcinoma risk - Jiankai Wei; Zhangxiu Liao; Ying Tao; Shuaiting Liu (BMC, 2023)
Abstract Purpose Programmed death-1 (PDCD-1) and lymphocyte activating 3 (LAG3), two important immunosuppressive molecules, play crucial roles in immune escape of tumor cells. This study evaluated the effects of PDCD-1 (rs10204525 and rs36084323), and LAG3 (rs870849 and rs1882545) gene polymorphisms on hepatocellular carcinoma (HCC) risk. Methods 341 patients with HCC and 350 cancer-free controls in the South Chinese population were included in a population-based case-control study. DNAs were extracted from peripheral blood samples. Genotypes were analyzed using multiplex PCR and sequencing. SNPs were analyzed using multiple inheritance models (co-dominant, dominant, recessive, and over-dominant). Results The allele and genotype frequencies of neither of the four polymorphisms, adjusted for age and gender, differed between HCC patients and controls. The differences were also not significant after stratifying by gender and age. According to our results, HCC patients with rs10204525 TC genotype had significantly lower AFP levels than HCC patients with rs10204525 TT genotype (P = 0.004). Moreover, the frequency of PDCD-1 rs36084323 CT genotype reduced the risk of TNM grade (CT vs. C/C-T/T: OR = 0.57, 95%CI = 0.37-0.87, P = 0.049). Conclusion Our results demonstrated that the PDCD-1 (rs10204525 and rs36084323), and LAG3 (rs870849 and rs1882545) polymorphism did not influence the risk of HCC, PDCD-1 rs10204525 TC genotype was associated with the lower AFP levels and rs36084323 CT genotypes were related to HCC tumor grades in the South Chinese samples.